Passive immunisation of post-weaned piglets using hyperimmune serum against experimental Haemophilus parasuis infection - Nedbalcova, K; Kucerova, Z; Krejci, J; Tesarik, R; Göpfert, Eduard; Kummer, V; Leva, L; Kudlackova, H; Ondriasova, R; Faldyna, M (Research in Veterinary Science, 2011)
The protective role of hyperimmune serum in the prevention of Haemophilus parasuis infections in post-weaned piglets was assessed by experimental challenge. The hyperimmune serum was obtained from a pig vaccinated with a commercial vaccine against Glässer's disease. Thirty-eight weaned piglets were divided into four groups: three groups were immunised intramuscularly with 10 ml of hyperimmune serum and one group consisted of unimmunised control animals. All piglets were subsequently infected intraperitoneally with H. parasuis serotype 5 at different times after immunisation. The use of hyperimmune serum provided the piglets with partial protection against experimental infection. The levels of protection indirectly depend on time between serum inoculation and challenge infection. The best protection of piglets against experimental infection was obtained in the group immunised 1 week before inoculation; the same group in which the highest levels of antibodies were detected at the time of challenge.
Keywords: Animals; Sus scrofa; odstavení; Humans; pasivní imunizace; Swine Diseases; Immunization, Passive; Swine; prasata; Enzyme-Linked Immunosorbent Assay; Czech Republic; protilátky bakteriální; Antibodies, Bacterial; tkáňová distribuce; Weaning; Tissue Distribution; Česká republika; Haemophilus parasuis; zvířata; hemofilové vakcíny; hemofilové infekce; Haemophilus Vaccines; lidé; ELISA; Haemophilus Infections; nemoci prasat; Polymerase Chain Reaction; polymerázová řetězová reakce